2019
DOI: 10.1038/s41598-019-51397-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic 10-formyltetrahydrofolate dehydrogenase regulates glycine metabolism in mouse liver

Abstract: ALDH1L1 (10-formyltetrahydrofolate dehydrogenase), an enzyme of folate metabolism highly expressed in liver, metabolizes 10-formyltetrahydrofolate to produce tetrahydrofolate (THF). This reaction might have a regulatory function towards reduced folate pools, de novo purine biosynthesis, and the flux of folate-bound methyl groups. To understand the role of the enzyme in cellular metabolism, Aldh1l1−/− mice were generated using an ES cell clone (C57BL/6N background) from KOMP repository. Though Aldh1l1−/− mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 72 publications
(82 reference statements)
4
22
0
1
Order By: Relevance
“…One of the goals of this study was to differentiate the function of the ALDH1L2 enzyme from the function of its cytosolic counterpart ALDH1L1. We previously reported that the Aldh1l1 KO in mice affected genes associated with inflammation [ 12 ]. The role of the folate metabolism in inflammation and immunity has been underscored [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the goals of this study was to differentiate the function of the ALDH1L2 enzyme from the function of its cytosolic counterpart ALDH1L1. We previously reported that the Aldh1l1 KO in mice affected genes associated with inflammation [ 12 ]. The role of the folate metabolism in inflammation and immunity has been underscored [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Experimental data suggest that this reaction is important for the regulation of the overall cellular folate pool as well as the proliferative capacity of the cell [ 10 , 11 ]. We have recently generated mice with targeted Aldh1l1 knockout and demonstrated that the animals lacking the enzyme display metabolic signs of folate deficiency and have impaired glycine metabolism in the liver [ 12 ]. The cause of these metabolic perturbations was the inability, in the absence of ALDH1L1, to convert 10-formyl-THF to THF resulting in the shortage of the latter metabolite required for the generation of glycine from serine [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…此外, 有研究表 明, 左旋肉碱合成过程中也能生成甘氨酸 [11] . 在甘氨 酸合成途径中, 丝氨酸合成甘氨酸以及甜菜碱转化为 甘氨酸的后两步反应依赖于叶酸, 其中10-甲酰基四氢 叶酸脱氢酶(肝脏中高度表达的叶酸代谢酶)可代谢10-甲酰基四氢叶酸产生四氢叶酸, 从而影响叶酸依赖的 甘氨酸生成 [12] .…”
Section: Figureunclassified